Analisis Kebutuhan Modul Ajar Pemanasan Global Berbasis PBL untuk Meningkatkan Keterampilan Pemecahan Masalah dan Self-Efficacy Siswa - Fajrin, Virgiani Pangestika; Wibowo, Firmanul Catur; Nasbey, Hadi (Jayapangus Press, 2024)
Global warming is a global challenge that requires deep understanding and active involvement of students in developing sustainable solutions. In an effort to support students' active involvement in the learning process, the government provides textbooks for teachers and students to use. However, the book still has shortcomings so it has not been maximized properly. This research aims to obtain information regarding the need for a global warming teaching module based on problem based learning to improve students' problem solving abilities and self-efficacy. The research method used was exploratory descriptive with research subjects namely 15 Tangerang City physics teachers and 30 students at Yuppentek 1 Tangerang High School. Data collection was carried out through distributing teacher and student needs questionnaires, problem solving skills tests, and student self-efficacy questionnaires via Google Form. The analysis technique used is quantitative. The results show that more than 50% of students have low problem solving abilities and self-efficacy. In addition, 50% of teachers and students need teaching modules to present material more clearly in the implementation of learning, providing a more systematic competency. So, it can be concluded that it is necessary to develop a problem-based learning-based global warming teaching module that can improve students' problem-solving abilities and self-efficacy.